Hubungan Status Gizi dan Usia Menarche dengan Kejadian Dismenorea pada Remaja Putri - Wirawanti, Ika Wirya (Wellness And Healthy Magazine, 2021)
Dysmenorrhea is a common complaint during menstruation, especially in adolescent girls which can interfere with their daily activities, especially at school. The purpose of this study was to determine the relationship between nutritional status and age of menarche with dysmenorrhea in adolescent girls. This research was quantitative research using a cross-sectional design. Data collection was carried out in January-February 2021. The research population was class IX students of SMP Negeri 17 Makassar with a total sample of 50 people. Sampling was carried out using the purposive sampling technique with inclusion criteria aged 12-15 years, already menstruating, and willing to become research subjects by signing informed consent. This study consisted of independent variables, which were nutritional status and age of menarche, and the dependent variable which was dysmenorrhea. The data was obtained directly by using a questionnaire to determine the age of menarche and the incidence of dysmenorrhea in adolescent girls, then using a height measuring device and weight scales to determine the nutritional status of adolescent girls based on the calculation of Body Mass Index (BMI). The data were analyzed using the chi-square test with SPSS. The results showed that based on the chi-square statistical test, there was a significant relationship between nutritional status and the incidence of dysmenorrhea with p value=0,005, while for age at menarche there was no significant relationship between age at menarche and the incidence of dysmenorrhea with p value=0.440. This showed that nutritional status was related to the incidence of dysmenorrhea in adolescent girls, which indicated that it was important to maintain normal nutritional status to avoid the incidence of dysmenorrhea, especially in adolescent girls.Dismenorea merupakan keluhan yang umum terjadi pada saat menstruasi khususnya pada remaja putri yang dapat mengganggu aktivitasnya sehari-hari utamanya di sekolah. Tujuan penelitian ini adalah untuk mengetahui hubungan status gizi dan usia menarche dengan kejadian dismenorea pada remaja putri. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan desain cross sectional. Pengumpulan data dilakukan pada bulan Januari-Februari 2021. Populasi penelitian yaitu siswi kelas IX SMP Negeri 17 Makassar dengan jumlah sampel penelitian sebanyak 50 orang. Pengambilan sampel dilakukan dengan menggunakan teknik purposive sampling dengan kriteria inklusi yaitu remaja putri berusia 12-15 tahun, sudah menstruasi, dan bersedia menjadi subjek penelitian dengan menandatangani informed consent. Penelitian ini terdiri atas variabel independen yaitu status gizi dan usia menarche, serta variabel dependen yaitu dismenorea. Data diperoleh secara langsung dengan menggunakan kuesioner untuk mengetahui usia menarche dan kejadian dismenorea pada remaja putri, kemudian menggunakan alat pengukur tinggi badan dan timbangan berat badan untuk mengetahui status gizi remaja putri berdasarkan perhitungan Indeks Massa Tubuh (IMT). Data kemudian dianalisis menggunakan uji chi-square dengan bantuan SPSS. Hasil penelitian menunjukkan berdasarkan uji statistik chi-square terdapat hubungan yang bermakna antara status gizi dengan kejadian dismenorea dengan nilai p=0,005, sedangkan untuk usia menarche tidak terdapat hubungan yang bermakna antara usia menarchedengan kejadian dismenorea dengan nilai p=0,440. Hal ini menunjukkan bahwa status gizi berhubungan dengan kejadian dismenorea pada remaja putri yang mengindikasikan bahwa penting untuk mempertahankan status gizi normal untuk menghindari kejadian dismenorea khususnya pada remaja putri.